Identification of Target Genes at Juvenile Idiopathic Arthritis GWAS Loci in Human Neutrophils - Li, Junyi; Yuan, Xiucheng; March, Michael E.; Yao, Xueming; Sun, Yan; Chang, Xiao; Hakonarson, Hakon; Xia, Qianghua; Meng, Xinyi; Li, Jin (Frontiers in Genetics, 2019)
Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease among children which could cause severe disability. Genomic studies have discovered substantial number of risk loci for JIA, however, the mechanism of how these loci affect JIA development is not fully understood. Neutrophil is an important cell type involved in autoimmune diseases. To better understand the biological function of genetic loci in neutrophils during JIA development, we took an integrated multi-omics approach to identify target genes at JIA risk loci in neutrophils and constructed a protein-protein interaction network via a machine learning approach. We identified genes likely to be JIA risk loci targeted genes in neutrophils which could contribute to JIA development.